Performance comparison of DFT, DCT and DWT based OFDM with wavelet family to minimize PAPR - Pinardi, Sofia; Ismail, Ahmad Fadzil; Hasan, Mohammad Kamrul; Abdullah, Khaizuran (African Journal Online, 2018)
The paper presents the analysis of peak average power ratio (PAPR) performance of wavelet based OFDM (WOFDM) using wavelet families. We study on several wavelet from different wavelet families to find out the PAPR performance. The WOFDM system using, Haar, Daubechies, Symlets, Coiflets, Biorthogonal, and discrete Meyer. WOFDM using QPSK modulation to reduce PAPR. Discrete Fourier transform (DFT) and discrete cosine transform (DCT) to compare discrete wavelet transform (DWT). These transform, that DCT with ‘Haar’ and ‘biorthogonal’ shows better improvement among the wavelet families since the PAPR achieve almost 5 dB.